Quarantine treatment by gamma radiation for different development stages of Callosobruchus maculatus in bean Vigna sinensis - ARTHUR, VALTER (2018)
The loss of stored grain caused by insects generates a problem of economic order of importance, due to concern about the increased supply of food for the world population is expanding. Associated with this fact, there is the problem of nutritional deficiency due to lack of protein, especially for the less privileged populations. The use of ionizing radiation in grains and products stored without a doubt can solve the problem of the losses in these products, since it does not induce resistance to insects and leaves no toxic residue in the products, and is considered an effective and safe method. The aim of the experiment was to determine the effect of ionizing radiation from cobalt-60 as a quarantine treatment for the different stages of development of Callosobruchus maculatus (Fabr., 1972) (Cole??ptera, Chysomilidae) in bean Vigna sinensis. The experiment was conducted in the laboratory of Radiobiology and Environment CENA / USP., Piracicaba, SP, Brazil. Bean samples infested with eggs, larvae, pre-pupae and pupae C. maculatus, the experiment consisted of 4 replicates for each stage of the insect's life cycle, and each repetition consisted of 20 individuals (eggs, larvae, pre-pupae and pupae), a total of 200 subjects per treatment which were irradiated with doses of 0 (control), 25, 50, 75 and 100 Gy, a source of cobalt-60, Gammabeam-650 type, in a rate dose of 1.3 kGy / h. The experiment was conducted in a room with a relative of 25 ?? 2 ?? C temperature and humidity of 70 ?? 5%. After 35 days of irradiation process were carried out evaluations of the number of insects emerged in each repetition within the treatments. From the results obtained it was concluded that the dose lethal to eggs and larvae was 25 Gy, while for pre-pupae was 50 Gy, to pupae 100 Gy was not sufficient to control the adult emergence.